Size matters: The impact of aid on institutions - Chakriya Bowman; Satish Chand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper proposes that aid flowing to smaller (less populous) countries has a negative impact on the quality of institutions in terms of performance and policy as opposed to that flowing to larger countries, where evidence suggests that the impacts are positive. The analysis here suggests that the level of development, the size of an economy, and the level of aid receipts matter for institutional performance as quantified by measures of economic freedom. Cross-country evidence is presented that suggests the impact of aid is damaging in small vis-à-vis large countries, and that, while aid increases economic freedom as a whole, the impact of aid on economic freedom is negative for nations with a population less than 1.4 million. This is significant for small island economies in the Pacific, where increasing amounts of overseas development assistance fund governance programmes. Case studies of Fijian economic governance initiatives are used to illustrate the difficulties encountered when donors fund institutional reform programmes in Pacific states.
Keywords: F35; F4; O11; O19; 330; Pacific islands; aid; growth; economic freedom index; institutions; Entwicklungshilfe; Kleines-Land-Modell; Insel; Governance-Ansatz